B Cells in Rheumatoid Arthritis: From Pathogenic Players to Disease Biomarkers. (29th April 2014) - Bugatti, Serena; Vitolo, Barbara; Caporali, Roberto; Montecucco, Carlomaurizio; Manzo, Antonio
Abstract : The therapeutic benefit of depleting B cells in rheumatoid arthritis (RA) has refocused attention on B cells with increasing awareness on their role in autoimmunity and their function beyond autoantibody production. The rapid increase in our comprehension of B-cell pathobiology is progressively opening novel perspectives in the area of B cell-targeted therapies with the expectation to define more specific approaches able to preserve the homeostasis of the humoral response while disrupting the pathogenic components. In parallel, B-cell activity in RA is starting to be explored in its clinical value, in search of novel biomarkers embedded in the pathogenic process that could help classifying the disease and predicting its heterogeneous outcome beyond inflammation dynamics. In this review, we summarize current knowledge on the multiple roles that B cells play in several aspects of RA. We also analyze their distribution and potential function in different anatomic compartments with specific reference to the main sites in which the disease may be sustained and exert its detrimental effects: the systemic circulation, synovium, bone marrow, and draining lymph nodes. We also highlight novel data encouraging further research in the field of biomarkers related to B cells and their regulatory factors.